State appropriations and performance of former Model C schools in South Africa - Hammond, Christopher Jon (My University, 2019)
ABSTRACT South African schools are under pressure to perform and provide their stakeholders with high quality teaching and learning. Former Model C schools have witnessed a decline in state appropriations, and many are battling to deliver the same level of performance that is consistent with their independent school competitors. Although the literature has identified the roles of School Governing Bodies (SGBs) as key role players in school performance, there is very little empirical research pertaining to additional role players such as past pupils and the school business manager. The aim of this study is to explore principals, SGB members and business manager’s current financial responsibilities and investigate which of these responsibilities has the greatest influence on performance. The study also attempts to analyse the causal mechanism of fluctuating state appropriations in order explore the relationship that exist between fluctuating state appropriations and performance (financial, pass rates and teacher-pupil ratios) in former Model C schools. Qualitative, exploratory research procedures were implemented to gain new insights into fluctuating state appropriations and the casual mechanism which affect performance. A total of 12 semi structured, in-depth interviews were conducted with principals, business managers and SGB members, all with senior levels of authority, from four different schools. The interviews lasted roughly 1 hour and were analysed through thematic content analysis. The key findings acknowledged the SGB’s as crucial players in school performance and reinforce their responsibility as game changers in the financial management training of former Model C schools SMTs. The literature paid tribute to their role in financial management but did not recognise other participants as stakeholders on which former Model C schools can depend. It was determined that developing the human capital; using a combination of rewards and recognition and recruiting and selecting qualified educators provided the best opportunity to improve these school’s performance. The findings from this research add to the existing literature in the field of state schooling and performance.
Keywords: Appropriations; performance; Model C schools